Growth and agar characteristics of selected Gracilaria species under different cultivation methods - Far, Fong Chuen
Culture of the commercially important agarophyte, Gracilaria using two different approaches was done. Cultivation via vegetative propagation of Gracilaria sp. and G. manilaensis was conducted in pond in Gelang Patah, Johore, using line and floating - cage methods while natural spore recruitment was implemented in the wild population of G. changii in Sandakan, Sabah on fixed - bottom rope and netting substrates with Phase 1 (PI) from June 2004 to June 2005 and Phase 2 (P2) from August 2004 to June 2005. In pond culture, line method supported better growth and productivity of Gracilaria sp. and G. manilaensis.